PENGALAMAN PELECEHAN SEKSUAL MAHASISWA DAN PENCEGAHANNYA - Nurfadhilah Nurfadhilah; Aisya Alawiyah (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2023)
Sexual violence in educational settings between 2015-2021 mostly occurred in tertiary institutions. Types of violence recorded were sexual violence 87.91 percent, psychological and discrimination 8.8 percent, and physical violence 1.1 percent. The method used in this study is a qualitative method with a phenomenological study design. Measurement of variables using in-depth interviews with three active students at Islamic universities in Jakarta. The results show that sexual education is very important in the campus environment, it can be used to stop various stigmas and normalize sexual violence. Sending photos with sexual nuances without the recipient's consent is a form of sexual harassment and can have a traumatic impact on the victim's life. Efforts that can be made include increasing awareness and education of sexual violence, conducting training programs for students and campus staff on gender equality and handling cases of sexual violence, establishing resource centers for victims, providing safe facilities, and implementing clear policies on protection against sexual violence.